EFFICIENCY VS THE MAQASID SHARIAH INDEX: A COMPARATIVE STUDY OF CONVENTIONAL AND ISLAMIC BANKS IN INDONESIA - Salman Al Parisi; Idqan Fahmi; Trias Andati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Over the last few years, Indonesian Islamic banking has experienced positive development, but there has been a dramatic dip in the growth of the assets and deposits of commercial Islamic banks. This indicates possible inefficiencies in these banks, and the sharp decline in the growth of their assets needs to be assessed in terms of efficiency and Islamic values, which are considered to be able to enhance performance. This research examines conventional and Islamic bank performance in terms of efficiency with data envelopment analysis (DEA) and the maqasid shariah index (MSI) with simple additive weighting (SAW) analysis, using data from fourteen commercial Islamic banks and four commercial conventional banks over the period 2007 to 2018. The results show that conventional banks were more efficient than Islamic ones, except in the financial crisis period, when the efficiency of Islamic banks was higher. In addition, the maqasid shariah index of conventional banks was lower than that of Islamic ones, although the index for Islamic banks was still very low. Furthermore, the study also found that the greater the level of total assets, the higher the maqasid shariah. Keywords: banking performance, commercial islamic banks, efficiency, maqasid shariah index